Analisis Wacana Kritis Atas Representasi Rakyat dalam Strategi Komunikasi Politik Kang Dedi Mulyadi - Denny Suryakusuma; Riana Putri; Alfi Dini Rahman; Ahmad Haikhal; Muh Ruslan Ramli (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the representation of the people in Kang Dedi Mulyadi’s social media content through the perspective of Critical Discourse Analysis using Teun A. Van Dijk’s model. Social media, particularly the YouTube channel “Kang Dedi Mulyadi Channel”, is utilized as a medium of political communication that presents narratives about the people and their leader. The findings reveal that the people are often represented as vulnerable, weak, and marginalized groups who require attention, protection, and swift action from a leader perceived as a savior. The political communication strategy employed is both populist and performative, making use of crisis narratives, local cultural symbols, and emotional expressions to foster a sense of closeness with society. Within the framework of critical discourse, this content reflects the existence of power relations and ideology that position the leader as the dominant actor in addressing social problems. These findings demonstrate that social media is not merely a space for interaction, but also a strategic instrument to construct the image of a leader, strengthen legitimacy, and shape public perception regarding the relationship between the people and those in power.